AB0713 PERIODONTAL DISEASES AND ITS ASSOCIATION WITH ANKYLOSING SPONDYLITIS/SPA: A SYSTEMATIC REVIEW. (2nd June 2020) - Pandey, A.; Ravindran, V.; Pandey, M.; Rajak, R.; Pandey, V.
Abstract : Background: A close association between periodontal disease and Ankylosing spondylitis (AS) has long been specualted. Both diseases are characterized by dysregulation of the host inflammatory response, leading to further destruction of soft and hard connective tissue with there being evidence of increased levels of TNF-α and various interleukins in both patients of AS and periodontitis. Objectives: The aim of this systematic review was to appraise the available literature exploring the relationship between AS and periodontal disease. Methods: We searched Medline & Embase databases (from their inception till October 2019) using appropriate combinations of following search items with limits '(English, Human)'; Ankylosing spondylitis, spondyloarthritis, spondyloarthropathies, spondyloarthritides, spinal disease, musculoskeletal disease, Rheumatic disease AND periodontitis, periodontal disease, periodontoses, parodontoses, chronic periodontitis, gum disease, gingivitis, oral health, dental health, plaque index, bleeding on probing, probing pocket depth, clinical attachment loss. This search was supplemented by the manual search of bibliographies of articles selected and conferences proceedings of EULAR. Only be reviews, observational study of cross-sectional, cohort or case control type on adult patients with AS were selected. Data was extracted from a predesigned proforma. A close association between periodontal disease and Ankylosing spondylitis (AS) has long been specualted. Both diseases are characterized by dysregulation of the host inflammatory response, leading to further destruction of soft and hard connective tissue with there being evidence of increased levels of TNF-α and various interleukins in both patients of AS and periodontitis. Results: A total number of 984 articles were identified and 12 were selcted for detailed appraisal (Figure 1, PRISMA flow chart). They were all case control studies. The prevalence of periodontitis ranged from 38% to 88% in patients with AS whereas in the control group from 26% to 71 % in controls. Out of 12 studies, two showed significant changes in Plaque Index (PI), two studies showed altered Pocket Probing Depth (PPD), three showed significant increased in Clinical Attachment Loss (CAL) and increased Bleeding On Probing (BOP) was seen in 2 studies. In 7 studies, periodontitis was seen in a significant number of patients with AS (P<0.05). All studies reported that the prevalence of periodontal disease in AS patients was higher as compared to non-AS patients. Conclusion: Our systematic review found an association between AS and periodontal disease. Patients with AS show higher prevalence of periodontitis and a poor oral hygiene as compared to healthy controls. At practice level, this systematic review underscores the need for a collaboration between dentists and rheumatologist. Disclosure of Interests: None declared